Mengapa Crafting Gagal? Workplace Belongingness sebagai Mata Rantai yang Hilang dalam Kesejahteraan Gen Z dan Milenial - Damayanti, Bella Febriana; Samian (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
This study aims to examine the mediating role of workplace belongingness upon the effect of job crafting and leisure crafting on employee well-being based on Self-determination Theory (SDT). The research employed a cross-sectional survey method using data from Gen Z and Millennial employees (N=121) working in hybrid settings in Indonesia. The analysis was conducted using a Generalised Linear Model (GLM) Mediation approach. The findings revealed that: (1) The direct effect of both job crafting and leisure crafting on employee well-being are not statistically significant, and (2) workplace belongingness fully mediates the effect of job crafting and leisure crafting on employee well-being. These results suggest that job and leisure crafting alone may be insufficient to improve employee well-being unless such efforts foster a strong sense of connection to the organization or company, as well as when employees feel integrated, appreciated, and valued within their work community.